The compact bedford introduction to literature : - Meyer, Michael (Bedford/St. Martins, 2009)
The Compact Bedford Introduction to Literature is designed to bring literature to life — and to make students lifelong readers. As an instructor of literature and writing, editor Michael Meyer understands that a particular challenge in today’s classroom is that students may not see literature as relevant to their lives. They may have difficulty reading it critically and lack confidence in their writing skills. With these factors in mind, Meyer has put together a lively collection of literature drawn from many periods, cultures, and voices, with an excellent representation of contemporary authors, women authors, and authors of color.